Comparison of diagnosis frequency between versions of the European Consensus on Sarcopenia: a cross-sectional study - Patrícia da Silva Klahr; Luis Fernando Ferreira; Cislaine Machado de Souza; Luis Henrique Telles da Rosa (Brazilian Society of Geriatrics and Gerontology, 2023)
Objective: To compare sarcopenia diagnosis according to 2 versions of the European Consensus on Sarcopenia (EWGSOP and EWGSOP2) in a sample of older adults. Method: This crosssectional study included 82 community-dwelling older people from Porto Alegre, Brazil. The patients were assessed by trained professionals and were classified according to the criteria of the 2 versions of the consensus to show the differences between the classification models. Results: The participants performed the Timed Up and Go test in < 7.21 seconds. On average,their performance on the 6-meter walk test was above the predicted value. Only 3 patients had a gait speed < 0.8 m/s. Handgrip strength was, on average, the predicted percentage. In the Short Physical Performance Battery, the scores of a few were intermediate but most were high. According to EWGSOP criteria, 92.18% were non-sarcopenic and 7.81% had severe sarcopenia, while according to EWGSOP2 criteria, 98.43% were non-sarcopenic, 1.56% were sarcopenic, and none had severe sarcopenia. The rate of sarcopenia diagnosis, which was 8.53% according to EWGSOP criteria, reduced to 3.65% according to EWGSOP2 criteria and the new cut-off points (p = 0.034). Conclusion: Although our sample was small, the reduction was significant, indicating that the change in criteria, even with lower cut-off points, reduced the probability of early diagnosis.